STOCK RETURN IN INDONESIA BANKING COMPANIES: INVESTMENT DECISIONS, DIVIDEND POLICY, INSTITUTIONAL OWNERSHIP, INTEREST RATE - Enggar Bayu Kusumaningrum; Hasna Noor Alifa; Amrie Firmansyah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2021)
This study aims to determine the effect of investment decisions, dividend policy, institutional ownership, and interest rates on stock returns. This research is a quantitative study using secondary data and multiple regression analysis methods. Data was sourced from www.idx.com and finance.yahoo.com consist of data and information from company financial statements and stock prices. Purposive sampling was chosen as the sampling method and obtained 35 banking companies for three years, so the total sample is 105 firm-year. The results suggest that investment decisions, dividend policy, and institutional ownership are not associated with stock returns, while interest rates negatively affected stock returns. This study indicates that banking companies make significant innovations in their products so that the investment objective is to support the company's operational activities and increase company value from investors' perspective.